CONTRIBUTION TO THE ARTIFICIAL MILK FEEDING OF LAMBS 3. Influence of the artificial milk composition on the production of heavy milkfed lambs - ΚΑΛΑΪΣΑΚΗΣ Π.; ΠΑΠΑΔΟΠΟΥΛΟΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 1974)
Three kinds of artificial milk have been tried for the fattening of lambs Friesland X Chios and Friesland X Local breed of Attica for the production of heavy weight milk - lamb carcass (60 days old). They were the following: 1) Artificial milk made by the Agricultural college of Athens (total protein 37,5"/0 DM. fat 30’/n DM). 2) Ewelac (total protein 25,5% DM, fat 31%, DM) and 3) Ewelac enriched with hydrolyzed casein (total protein 37°/0 DM, fat 26°/0 DM), The milk substitutes were reconstituted to contain 20°/QDM. The liquid diets were offered individually two times per day (each time 600 g) at body temperature. Dry pelleted feed (630 S.U , 180 g D.P. per kg DM) and water were available after the 15th day. The quantities fed was adjusted to a total consumption of 7-8 kg DM per lamb. Results have shown that the artificial milk of commerce iEwelacj. supplied as above, produces in the case of Friesland X Local breed lambs satisfactory yields with final weight 18- 19 kg. Jn the case of lambs Friesland X Chios heavier weights are obtained (21 -22 kg) but the fattening conditions of the carcass is not satistactory. Enrichment of the artificial milk of commerce with hydrolysed casein does not prove to be worth while.